Dance as a tool for emotional well-being - Conchar, Lauren (Rhodes University, Faculty of Humanities, Department of Psychology, 2017)
Dance has numerous benefits for emotional well-being. For young people specifically it can serve as a prosocial activity where they can engage in a purposeful activity, in a safe space with consistent boundaries and discipline, while surrounded by peers, teachers and positive role models. Recreational spaces that allow young people to feel safe and express themselves is especially important in low socioeconomic areas where there are limited resources and exposure to heightened levels of crime as young people may be less likely to engage in negative behaviours when they have access to alternative, positive activities. This research aimed to explore the lived experiences of a group of young people who participate in dance classes at a community dance project in the Western Cape. The sample group consisted of four young people between the ages of 16 and 20. Semi-structured interviews were conducted with the participants and the interviews were analysed using interpretative phenomenological analysis. Three major themes emerged from the data, namely 1) My exposure to dance - The impact of context, 2) What motivates me to continue attending classes - The fulfilment of the three basic psychological needs, and 3) How does dance make me feel - The experience of emotional well-being through dance. The discussion of the findings yielded many similarities between the experiences of the participants and the relevant literature. Further, it appears that all four participants experience the satisfaction of the three basic psychological needs (competence, autonomy and relatedness) at the centre. This may serve as a motivator to continue attending classes as well as contribute to sustained eudaimonic wellbeing. Recommendations include further studies being conducted with groups of young people engaging in dance projects in different socioeconomic contexts and in different parts of South Africa. This could give us a more rounded understanding of how people young people experience dance class and how it contributes to emotional well-being. Further research could also be conducted with recreational projects that offer other activities in under-resourced areas in order to better inform the development of such recreational activities.
Keywords: Dance therapy; Well-being; Happiness; Adolescent psychology; Dance -- Social aspects -- South Africa -- Cape Flats; Dance -- Psychological aspects -- South Africa -- Cape Flats; Dance -- Psychological aspects -- South Africa -- Cape Flats -- Case studies; Community development, Urban -- Psychological aspects -- South Africa -- Cape Flats -- Case studies